Ratcheting-fatigue behavior of trabecular bone under cyclic tensile-compressive loading. (December 2020) - Lin, Xianglong; Zhao, Jie; Gao, Lilan; Zhang, Chunqiu; Gao, Hong
Abstract: This study aims to investigate the ratcheting-fatigue behaviors of trabecular bone under cyclic tension-compression, which are produced due to the accumulations of residual strain in trabecular bone. Simultaneously, the effects of different loading conditions on ratcheting behaviors of trabecular bone were probed. It is found that the gap between ratcheting strains under three stress amplitudes will gradually widen. As the stress amplitude increases, the ratcheting strain also increases. Mean stress has a significant effect on the ratcheting strain. When the mean stress is 0 MPa and 0.155 MPa, the ratcheting strain increases with the number of cycles. However, when the mean stress is -0.155 MPa, the ratcheting strain decreases as the cycle goes on. The existence of double stress peak holding time causes the creep deformation of trabecular bone, which leads to the increase of ratcheting strain. It is also noted that the ratcheting strain is greatly increased with prolongation of stress peak holding time. The digital image correlation (DIC) technique was applied to analyze the fatigue failure of trabecular bone under cyclic tension-compression. It is found that the increase of stress amplitude accelerates the damage of sample and further reduces its fatigue life. Cracks are observed in trabecular bone sample, and it is noted that the crack propagation is rapid during cyclic loading.